Roxadustat in CKD and transplant patients: A new era in anemia management - Khan, Muhammad Tassaduq; Rashid, Sidrah; farooq, Syed Hasan; Sabahat Sarfaraz; Hamid, Rashid bin; Naranjan Lal (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
The aim of this study was to evaluate the efficacy and safety of Roxadustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI), for the management of anemia in patients with chronic kidney disease (CKD), including hemodialysis-dependent (HDD), non-dialysis-dependent (NDD), and renal transplant recipients (RTRs). This was a prospective cross-sectional study was conducted at Dow University of Health Sciences, Karachi, Pakistan, from August 2024 to January 2025. A total of 55 patients were enrolled and treated with Roxadustat, beginning with a dose of 100 mg thrice weekly for the initial 4 weeks, followed by 70 mg thrice weekly. The primary outcome was the achievement of a hemoglobin (Hb) target of ?10 g/dL within 6 weeks. The safety profile was assessed by monitoring adverse events, including myocardial infarction. A total of 55 patients were recruited in the study. Of these, 19 were hemodialysis-dependent (HDD), 31 were non-dialysis-dependent (NDD), and 5 were renal transplant recipients (RTRs). The hemoglobin target of 10 g/dL within 6 weeks was achieved in 48 patients (87.3%). Among the successful cases, 18 were HDD patients, 26 were NDD patients, and 3 were RTRs. The remaining 7 patients (12.7%) did not achieve the target hemoglobin level within the specified timeframe. Adverse events were observed in 3 patients (5.4%), all of whom experienced myocardial infarction. This included 2 HDD patients and 1 NDD patient. No adverse events were reported in the RTR group. Overall, Roxadustat was well-tolerated, with a structured dose adjustment from 100 mg thrice weekly to 70 mg thrice weekly ensuring sustained hemoglobin levels. Roxadustat appears to be an effective and generally safe therapeutic option for managing anemia in CKD patients, including those who are HDD, NDD, or RTRs. However, monitoring for cardiovascular events, such as myocardial infarction, is essential in these patients.